STRATEGI PENDEKATAN ARSITEKTUR BIOFILIK DALAM FASILITAS AGROINDUSTRI UNTUK MEMPERTAHANKAN KUALITAS PADI DAN JAGUNG DI KECAMATAN KALITIDU KABUPATEN BOJONEGORO - Arif, Muh. Zainal; Faisal, Muhammad; Kusumaningayu, Intan (CV SWA Anugerah, 2025)
Bojonegoro Rule is one of the zones in East java that’s experiencing improvement in the midst of the potential for flooding all through most of the year. Bojonegoro Rule has 28 sub-districts, 11 sub-districts and 419 towns. Regional economic development may be a handle where territorial government and the community oversee existing resouces and frame a partnership design between regional government and the private division to form occupations. Agroindustri may be a arrangement, not as it were crearing employments but moreover expanding yield from the agrarian division.